A 62-year-old Man with Chondroblastic Osteosarcoma of Maxilla: A Rare Case - Sedigheh Bakhtiari; Robab Noormohammadi; Fatemeh Mashhadi abbas; Kosar Rezaei far (Mashhad University of Medical Sciences, 2018)
Osteosarcoma (OS) is a malignant tumor that induces formation of osteoid or immature bone and rarely occurs in maxilla. Maxillofacial OSs are reported to occur in the third to fifth decades that is 1-2 decades later than the mean age for OS of long bones. The present case is a 62-year-old man with facial asymmetry and pain in his left upper jaw. Intraoral examination showed a bony hard, tender swelling about 50 x 60 mm in diameter in the maxillary alveolar ridge extending unilaterally from the maxillary incisor to the molar region which had expanded the buccal and palatal aspects of alveolar ridge. Computed tomography showed a hyper dense mass in the left maxilla extending to maxillary sinus. The diagnosis of OS was confirmed by histopathologic evaluation. Following the initial surgery, a local recurrence developed in the facial region of the patient within 18 months. Radiographic evaluation of OS of maxilla is important for diagnosis. Early diagnosis and radical surgery are the keys to increasing survival rate.